Influence of prescription charges on repeat prescribing in primary care - Bradley, F.; Elvey, R.; Ashcroft, D. M.; Noyce, P. (Journal of clinical pharmacy and therapeutics, 2007)
Summary Background:  Repeat dispensing by community pharmacists has now been rolled out nationally within England in order to improve patient convenience and reduce doctors’ workload. Little is known about how the charge status of the patient may impact on the uptake and prescribing practices of this service. Objective:  To examine whether the charge status of the patient influences the length of the repeat prescribing cycle. Method:  Thirty‐six community pharmacies collected data on repeatable prescriptions dispensed over a 4‐month period. A purposive sample of 13 general practices actively involved as pathfinder sites were selected for interview, to explore views on repeat prescriptions and influence of prescription charges. Results:  Completed audit forms were collected on 4029 repeatable prescriptions. Differences in the length of the prescribing interval between charge payers and exempt patients were found to be statistically significant (Mann–Whitney U‐test, P < 0·001), indicating that prescribers were issuing prescriptions for longer interval periods for charge payers. Thirteen general practitioners (GPs) and three practice managers were interviewed across 13 practices. Some GPs varied their prescribing to minimize the cost to patients. Others were motivated to reduce waste and promoted 28‐day prescribing for all patients. Conclusion:  The study has shown that charge paying patients are more likely to have longer prescribing intervals and that cost to the patient is a consideration for GPs when making these decisions. Future work should explore the influence of other factors such as age, socio‐economic status and patient morbidity on prescribing in primary care.